2018
DOI: 10.1080/09537104.2018.1499886
|View full text |Cite
|
Sign up to set email alerts
|

Administration of testosterone improves the prothrombotic and antifibrinolytic parameters associated with its deficiency in an orchidectiomized rat model

Abstract: This study investigated the effect of testosterone deficiency and replacement on platelets function and aggregation, coagulation, and fibrinolysis in young adult healthy male rats. Rats were classified into three groups (n = 6/group) of either "a sham-operated+ vehicle," "an orchidectomized (ORX)+ vehicle," and "an ORX+testosterone propionate (0.5 mg/kg, 3X/week, S.C)." All treatments were carried out for 12 weeks. Our results showed that ORX rats had induced platelets aggregation and coagulation and inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…A study of transgender men receiving TRT demonstrated decreased prothrombin concentrations in line with our findings ( 26 ). The decrease in FVII and prothrombin induced by TRT is in accordance with previous findings in animal studies ( 27 , 28 , 29 , 36 , 37 , 38 ). The influence of TRT on FX has not been addressed in other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A study of transgender men receiving TRT demonstrated decreased prothrombin concentrations in line with our findings ( 26 ). The decrease in FVII and prothrombin induced by TRT is in accordance with previous findings in animal studies ( 27 , 28 , 29 , 36 , 37 , 38 ). The influence of TRT on FX has not been addressed in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Another study on AAS abuse demonstrated reduced contact-induced kallikrein generation in terms of peak kallikrein concentration and endogenous kallikrein potential (EKP) in current abusers compared with former abusers and controls ( 25 ). Conversely, TRT of transgender men (born women) is not associated with a procoagulant state ( 26 ) and TRT given to castrated male rats normalizes the castration-induced increase in prothrombin and coagulation factor VII (FVII) concentrations ( 27 ). Earlier studies report reduced concentrations of prothrombin in TRT-treated rats ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of testosterone on coagulation following trauma are not well-described; overall, testosterone has been associated with tissue plasminogen activator, a known stimulator of fibrinolysis 17 and inversely correlated with plasminogen activator inhibitor, fibrinolysis inhibitor, fibrinogen, and endogenous thrombin potential. [17][18][19][20] In this study, one of the most striking changes in coagulation was illustrated by the change in LY30 among postpubertal females, with older females displaying significantly less fibrinolysis following trauma than prepubertal children or postpubertal males. Many postpubertal females experienced fibrinolysis shutdown after trauma, another finding that warrants further investigation as there are different subtypes of this phenomenon with distinct sequelae.…”
Section: Discussionmentioning
confidence: 71%
“…These data have been confirmed in a study conducted in castrated older men showing a lower maximum platelet aggregation response 98 . However, contrasting results have been shown in subsequent animal studies 99‐102 . In castrated rats, the restoration of the physiological doses of androgens inhibited oxidative stress‐induced platelet aggregation and reduced TXA2 release from platelets 100 .…”
Section: Methodsmentioning
confidence: 77%
“…98 However, contrasting results have been shown in subsequent animal studies. [99][100][101][102] In castrated rats, the restoration of the physiological doses of androgens inhibited oxidative stressinduced platelet aggregation and reduced TXA2 release from platelets. 100 Moreover, T could inhibit platelet aggregation via increased NO synthesis, which is associated with endothelial cell growth.…”
Section: Primary Hemostasismentioning
confidence: 99%